Optimización de los fluidos de perforación de agua utilizados en un campo de crudo pesado en la cuenca de los Llanos Orientales mediante el uso de nanotecnología (2020)
The objective of this work is to improve the drilling fluids currently used in the field through the use of nanoparticles to minimize formation damage and thus increase the profitability of the project. For this, the formulation of different water-based muds at different concentrations of nanoparticles (0.25%, 0.5% and 1%) was carried out to be subsequently evaluated at the laboratory level using API tests and determine the mud that presented the best performance. Once the tests were run, it was determined that the drilling fluid that had the best chemical and physical performance was “Mud 2” with 1% in addition to nanoparticles. Once the fluid performance was verified, the effect of the fluid on the wettability of the rocks was evaluated. For this, wettability tests were carried out in synthetic plugs wetted to both water and crude oil and it was determined that the mud filtrate satisfactorily improved the affinity of the rock to the water, thus facilitating the flow of crude oil along the formation by increasing the contact angle from 32 ° to 40 °. Then, the financial viability of the nanofluid with respect to the base mud was projected through the indicators Internal Rate of Return and Net Present Value. Based on this, it was determined that although nanofluid would increase costs by 10%, this would present greater profitability over time by allowing an increase in production associated with formation damage.